STUDY ON NONLINEAR DYNAMICS OF ASYMMETRICAL SUPPORTED ROTOR UNDER INFLUENCE OF HEELING ANGLE - LI Mo; LIU YongBao; WANG Qiang (Jixie qiangdu)
This paper takes the support structure of a low-pressure rotor system of a marine gas turbine as the background.Considering the heel angle of the rotor system,a dynamic model of the rotor supported by asymmetric rolling bearing is established. The variable-step fourth-order Runge-Kutta method was used to solve the system’ s dynamic equations,and the nonlinear theory were used to analyze the simulation results. The study shows that the heel angle has no effect on the stability of the system at low rotational speeds. At high rotational speed,the heel angle mainly affects the 1/2 harmonic of the system,and the system has a single chaotic island or two chaotic islands. When the left or right tilt angle of the rotor system is the same,the heel angle has the same effect on the nonlinear dynamics of the system. The research results can provide a theoretical basis for the design,monitoring and fault diagnosis of the rotor system.